GERAKAN SOSIAL PETANI DESA BANJARANYAR DALAM MEMPERJUANGKAN LAHAN PERTANIAN - Nanang Hasan Susanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This study was aimed to determine the history of social movements of Banjaranyar farmers, examined political economy theories of Popkin (1979) in The Rational Peasant: The Politics Economy of Rural Society in Vietnam that the resistance movement of farmers occurred when most people feel disadvantaged, and examined the theory of Scott (1976)about the concept of leadership and social structure. Through a historical approach, with the observation method of participation (participant observation) on the field, the study concluded, that the history of the struggle of Banjaranyar Farmers had a genuine dynamic, and the political economy theory of Popkin (1979), the theory of Scot (1976) manifested in social history that took place in the village of Banjaranyar.